Supervision stress: The psychological impact of poor supervision on postgraduate students - A qualitative single-case study design. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Background Postgraduate students often encounter significant academic pressures, with poor supervision emerging as a critical yet underexplored contributor to psychological distress. Inadequate supervisory support, inconsistent communication, and delayed feedback can severely hinder research progress while intensifying stress, anxiety, and burnout. Although research indicates a strong correlation between supervisory relationships and student mental health, institutional responses, particularly in resource-constrained South African universities, remain insufficient. Methods A qualitative single-case study design was employed at a South African public university. Data were gathered through semi-structured interviews and focus groups involving 20 participants: 12 postgraduate students, 5 academic supervisors, and 3 postgraduate program coordinators. Purposive sampling ensured participants had relevant supervisory experience. The thematic analysis focused on emotional strain, academic delays, coping mechanisms, and institutional responses. Results Eighty percent (80%) of students reported moderate to severe emotional stress linked to poor supervision. Common stressors included infrequent feedback, unclear research direction, and supervisor unavailability. Students frequently expressed feelings of isolation, self-doubt, and, in some cases, depression. Supervisors cited high workloads and limited training as barriers to effective supervision. Coordinators acknowledged the absence of institutional tools to track student well-being or assess supervisory effectiveness. Conclusion The study demonstrates that poor supervision is a significant driver of psychological distress among postgraduate students. Despite the risks, institutions often lack proactive mechanisms to support student mental health or improve supervisory practices. Recommendations Universities should implement compulsory supervision training that incorporates mental health awareness, communication, and conflict resolution. A centralized system for monitoring supervision quality and student well-being is essential. This should include timely feedback, accessible complaint processes, and mental health support. Regular supervisor evaluations based on student feedback are crucial to promoting accountability and enhancing postgraduate experiences.